A Method for the Quantification of Alkali and Alkaline Earth Metallic Species in Bioslurry Fuels - Zhang, Mingming; Gao, Xiangpeng; Wu, Hongwei (American Chemical Society, 2013)
This study reports a method for the quantification of alkali and alkaline earth metallic (AAEM) species in bioslurry fuels. The so-called evaporation-ashing-digestion-ion chromatography (IC) method consists of four steps, including evaporation that converts bioslurry into solid-like residue, ashing that converts the residue into ash, acid digestion that dissolves the ash into a solution, and IC analysis that quantifies the AAEM species in the solution. The novelty of the method is the combination of the evaporation step with the existing ashing-digestion-IC method that is developed for solid fuels but notsuitable for bioslurry fuels. The evaporation step consists of multi-steps of slow heating and holding at various segment temperatures corresponding to the boiling points of the major compounds in bio-oil, resulting in progressive evaporation of biooil vapors with little carry-over of biochar particles. The method has been successfully applied for quantifying AAEM species in bioslurry fuels with various biochar loading levels (5-20 wt %), with small relative standard errors (within ±3%) and low limitations of quantification (0.4-3.0 ppm). It also overcomes the biochar incomplete oxidation issue associated with the microwave-digestion-based methods, which considerably underestimate the concentrations of AAEM species in bioslurry fuels.